The Plasma Universe: A Coherent Science Theme for Voyage 2050 - Verscharen, Daniel; Wicks, Robert T.; Branduardi-Raymont, Graziella; Erdélyi, Robertus; Frontera, Filippo; Götz, Charlotte; Guidorzi, Cristiano; Lebouteiller, Vianney; Matthews, Sarah A.; Nicastro, Fabrizio; Rae, Iain Jonathan; Retinò, Alessandro; et al. (Frontiers in Astronomy and Space Sciences, 2021)
In review of the White Papers from the Voyage 2050 process and after the public presentation of a number of these papers in October 2019 in Madrid, we as White Paper lead authors have identified a coherent science theme that transcends the divisions around which the Topical Teams are structured. This note aims to highlight this synergistic science theme and to make the Topical Teams and the Voyage 2050 Senior Committee aware of the wide importance of these topics and the broad support that they have across the worldwide science community.